Thresholds of external flows for inclusive human development in Sub-Saharan Africa - Simplice Asongu; Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2019)
This research investigates the incidence of enhancing external flows on inclusive human development in a panel of 48 countries in sub-Saharan Africa. It complements the literature by examining the relevance of enhancing three types of external flows, namely: development assistance, foreign investment and remittances. Ordinary Least Squares, Tobit, Fixed effects, Generalised Method of Moments and Quantile regressions are used as empirical strategies. The following main results are apparent: (i) between 60 and 150 (% of GDP) is the threshold of foreign aid; (ii) 33.333 (% of GDP) is the foreign investment threshold and (iii) 25 (% of GDP) is the critical mass of remittances. At the established critical masses or thresholds, external flows start having positive effects on inclusive human development. Countries characterized by inclusive development levels that are low need more investment in foreign aid for inclusive human development compared to their counterparts characterized by inclusive human development levels that are high.
Keywords: F21; F24; F35; I30; O55; 330; Foreign investment; Remittances; Foreign aid; Inclusive development; Africa